ANALYSIS OF THE INFLUENCE OF SERVANT LEADERSHIP AND DIGITAL LEADERSHIPON EMPLOYEE PERFORMANCE WITH COMPETENCE AS AN INTERVENING VARIABLE IN THE SERVICE HEALTH IN LANGSA CITY - Khairina; Faisal Matriadi; Ikramuddin; Marbawi; Mariyudi; Yulius Dharma; A Hadi Arifin (RADJA PUBLIKA, 2024)
This study aims to Analyze The Effect Of Servant Leadership And Digital Leadership On Employee Performance With Competency As An Intervening Variable In The Health Office In Langsa City.The sampling method used in this study is the saturated sampling method. The saturated sampling method is a sampling technique when all members of the population are used as samples. The number of samples in this study was 148 respondents, because the total number of the population used as a sample was 148 respondents. The influence of Digital Leadership, Servant leadership on employee competence at the Langsa City Health Office. The influence of competence, Digital Leadership, Servant leadership on employee performance at the Langsa City Health Office. Competence is able to partially mediate the relationship between the Servant leadership variable and employee performance. Competence is able to partially mediate the relationship between the Digital leadership variable and employee performance.